2015
DOI: 10.1016/j.freeradbiomed.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking mtDNA damage and aging

Abstract: In the last century, considerable efforts were made to understand the role of mtDNA mutations and of oxidative stress in aging. The classic mitochondrial free radical theory of aging, in which mtDNA mutations cause genotoxic oxidative stress, which in turn creates more mutations, has been a central hypothesis in the field for decades. In the last few years, however, new elements have discredited this original theory. The major source of mitochondrial DNA mutations seems to come from replication errors and fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
113
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 144 publications
(118 reference statements)
0
113
0
1
Order By: Relevance
“…However, other studies suggest that heteroplasmy, the condition in which one cell possesses more than one mitochondrial genome, must increase to 70-90% of mtDNA within a tissue (Fayet et al, 2002;Trifunovic and Larsson, 2008), before mitochondrial respiratory function is reduced. This level of change in heteroplasmy is not typically observed with ageing (Rossignol et al, 2003;Pinto and Moraes, 2015). As mtDNA damage does not appear to affect the bioenergetic capacity of an individual until significant damage has accumulated, mtDNA damage would be predicted to have delayed negative consequences on the bioenergetic capacity of an individual, whether it occurred through oxidative damage or mtDNA replication error.…”
Section: Box 1 Possible Consequences Of Reproduction On An Individuamentioning
confidence: 93%
See 1 more Smart Citation
“…However, other studies suggest that heteroplasmy, the condition in which one cell possesses more than one mitochondrial genome, must increase to 70-90% of mtDNA within a tissue (Fayet et al, 2002;Trifunovic and Larsson, 2008), before mitochondrial respiratory function is reduced. This level of change in heteroplasmy is not typically observed with ageing (Rossignol et al, 2003;Pinto and Moraes, 2015). As mtDNA damage does not appear to affect the bioenergetic capacity of an individual until significant damage has accumulated, mtDNA damage would be predicted to have delayed negative consequences on the bioenergetic capacity of an individual, whether it occurred through oxidative damage or mtDNA replication error.…”
Section: Box 1 Possible Consequences Of Reproduction On An Individuamentioning
confidence: 93%
“…The relative importance of accumulating mtDNA damagewhether via oxidative damage or replication error -to the function of mitochondria is an area of intense debate (Pinto and Moraes, 2015). Some studies have shown the predicted negative change in mitochondrial respiratory function with moderate levels of mtDNA damage (Trounce et al, 1989).…”
Section: Box 1 Possible Consequences Of Reproduction On An Individuamentioning
confidence: 99%
“…Whılst the trajectory of aging can differ among older people (1), there is general agreement that aging is associated with an accumulation of cellular damage (2). The pathophysiological changes associated with aging can lead to mitochondrial dysfunction, failure of tissue repair mechanisms, accelerated cellular senescence, in addition to a reduction in tissue homeostasis, which may increase the risk of organ failure and mortality (3).…”
Section: Introductionmentioning
confidence: 99%
“…The main features of frailty traditionally include low physical activity levels, slowness in motor performance, and weakness, which may occur due to a loss of skeletal muscle mass and functioning (8)(9)(10). Furthermore, OS might lead to an activation of apoptotic pathways leading to cellular damage, aberrations in the expression of many transcription factors responsible for shifting protein synthesis to protein degradation, a decline in mitochondrial function, and an impairment of repair mechanisms (2,11). These interacting pathways may contribute to the detrimental effects of OS on muscles, bones, and the immune system (12).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from several tissues also suggests that the stem cell functional output is altered during aging [16]. The effect of aging on the regenerative ability of living organisms and its impact on biological activities has been the focus of many previous studies [17,18] but few, if any, authors have investigated the effect of age on either fetal stem cells in general or specifically on umbilical cord stem cells.…”
Section: Introductionmentioning
confidence: 99%